EXPERIMENTAL INVESTIGATION OF HEAT TRANSFER ENHANCEMENT OF CORRUGATED TWISTED TAPE INSERT WITH CFD ANALYSIS - K. G. KULKARNI; S. Y. BHOSALE; S. N. SATPUTE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The need to increase the thermal performance of heat exchangers, thereby affecting energy, material & cost savings have led to development & use of many techniques termed as Heat transfer Augmentation. Augmentation techniques increase convective heat transfer by reducing the thermal resistance in a heat exchanger. Twisted tapes-a type of passive heat transfer augmentation techniques have shown significantly good results in past studies. Different designs of twisted tapes used are-Reduced width twisted tapes (RWTT), Baffled reduced width twisted tapes (BRWTT1) & Baffled reduced width twisted tape with holes (BRWTT2). The proposed work is aimed at finding the heat transfer performance in a circular pipe by employing corrugated twisted tapes& also results are to be compared with plain twisted tape. These tapes will be tested for different configurations of twist ratios & wave angles. It is to be verified whether corrugated nature of twisted tape assists the heat transfer by turbulence enhancement or if it increases the pressure drop. Also the use of „CFD? software is proposed for analysis work & developing correlations. Heat transfer augmentation techniques (passive, active or a combination of passive and active methods) are commonly used in areas such as process industries, heating and cooling in evaporators, thermal power plants, air-conditioning equipment, refrigerators, radiators for space vehicles, automobiles, etc. Passive techniques, where inserts are used in the flow passage to augment the heat transfer rate, are advantageous compared with active techniques, because the insert manufacturing process is simple and these techniques can be easily employed in an existing heat exchanger. In design of compact heat exchangers, passive techniques of heat transfer augmentation can play an important role if a proper passive insert configuration can be selected according to the heat exchanger working condition (both flow and heat transfer conditions). In the past decade, several studies on the passive techniques of heat transfer augmentation have been reported. The present paper is a review on progress with the passive augmentation techniques in the recent past and will be useful to designers implementing passive augmentation techniques in heat exchange. Twisted tapes, wire coils, ribs, fins, dimples, etc., are the most commonly used passive heat transfer augmentation tools.